The Socio-Economic and Environmental Impact of Herdsmen Strike on Agriculture in Selected Local Government Areas in Benue ,Ebonyi ,Delta ,Kogi and Plateau State of Nigeria - Nathan Udoinyang; Iriaka Ndidi Scholastica; Reuben Daniel (International Journal of Global Sustainable Research, 2024)
This research looks at the socio-economic and environmental impact of herdsmen strikes on agriculture in selected local government areas of Benue, Delta, Ebonyi, Kogi and Plateau States in Nigeria. The research used both primary and secondary data to compile its population, which consists of the entire population of the selected local government areas of Agatu, Makurdi, Ughelli North, Aniocha North, Ebonyi, Ohaukwu, Omala, Dekina, Mangu and Bokkos making a total of 2,007,038. A sample size of 400 was achieved by using the Taro Yamane formula. With the use of a purposive sampling methodology, 400 questionnaires were circulated and 291 were collected. Using a mean criterion of 3.0, the questionnaire was evaluated using a 5-point Likert scale. The study recommended that the state and federal government of Nigeria should engage peace and conflict resolution experts in dealing with issues concerning herdsmen-farmer crises, adoption of community policing to forestall peace in the rural areas, designate some areas as grazing fields for the nomadic herdsmen and also adopt the use of PIGOVIAN TAX on the activities of herdsmen etc. The study concluded that agricultural activities will experience more employment, sales, revenue, profitability, and productivity in the absence of herdsmen attacks which in return will lead to economic growth and development of the LGS's, state and nation as a whole.Keywords: Agricultural activities, Environmental, Herdsmen, Socio-economic, Strike.